THE EFFECT OF SOCIAL MEDIA MARKETING ACTIVITIES ON CUSTOMER ENGAGEMENT, MEDIATED BY SOCIAL TIES AND PRODUCT ATTRIBUTES: A STUDY OF PO.BEJEU - Annatasya Nabila De Vega; Mohamad Rifqy Roosdhani (Branding: Jurnal Manajemen dan Bisnis, 2026)
This study aims to analyze the effect of social media marketing activities (SMMA) on customer engagement, with social ties and product attributes serving as mediating variables at PO Bejeu. The research employs a quantitative approach using a survey method targeting TikTok users who have viewed or interacted with content from PO Bejeu’s official account. The sampling technique used was purposive sampling, with a total of 239 respondents. Data were analyzed using Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) with the assistance of SmartPLS 4 software. The results indicate that SMMA has a positive and substantial effect on customer engagement, social ties, and product attributes. Social ties were found to have a positive and substantial effect on customer engagement and mediate the relationship between SMMA and customer engagement. Conversely, product attributes do not have a substantial effect on customer engagement and do not act as a mediating variable. These findings indicate that customer engagement on PO Bejeu’s social media is more influenced by the strength of social relationships among users than by perceptions of the service attributes offered. The implications of this study emphasize the importance of social interaction-based marketing strategies to enhance customer engagement on social media platforms.